Evaluation of Strategic Factors in HRD Practices of Nepali Banks: Towards Building an SHRD Model - Arhan Sthapit (AIBPM Publisher, 2020)
In view of a long-felt need to adopt the strategic factors of human resource development (HRD), this paper explores and evaluates the presence of strategic HRD factors instrumental to achieve theoretical HRD outcomes, and devise an SHRD model. An exploratory and analytical research approach was adopted to study all 25 non-state-owned commercial banks and all 14 national level development banks of Nepal through a questionnaire survey (July–December 2018) on 708 incumbent supervisors and managers chosen through a proportionate, stratified probability-sampling technique from (a) hierarchy-based strata, and (b) bank categories. A principal component analysis (PCA) was performed on 25 theoretically recognised strategic factors in current HRD practices; out of which 23 factors were identified as influential, and factor-labelled by the PCA into a three-factor model based on a regression analysis. The SHRD model factors so devised should prove instrumental to HR managers in strategically managing their HRD function for achieving expected HRD outcomes.